(untitled) (Bangladesh Journal of Zoology, 2015)
The activity patterns of pied kingfisher (Ceryle rudis Linnaeus, 1758) and stork-billed kingfisher (Pelargopsis capensis Linnaeus, 1766) were studied in the Chittagong University Campus, Chittagong, Bangladesh, during January 2011 to December 2013. Eight activities (resting/perching, bathing, flying, feeding, calling, preening, hovering and diving) were observed in this study, of which pied kingfisher performed all eight activities and stork-billed kingfisher performed all except bathing and hovering. Both kingfisher species spent the maximum (pied kingfisher: 31.87%; stork-billed kingfisher: 45.82%) time in resting/perching and the minimum (pied kingfisher: 4.83%; stork-billed kingfisher: 1.90%) in preening. Pied kingfishers were mostly (28.3%) active during 0700 and 0900 h and stork- billed kingfishers were more (31.17%) active in between 0901-1100 h. Pied kingfishers spent their highest (9.01%) time in different activities in August and the lowest (7.68%) in February, whereas storkbilled kingfishers spent the maximum (8.69%) time in March and the minimum (7.80%) in May. Bangladesh J. Zool. 42(2): 191-203, 2014